Integration of Multicultural Values in the Islamic Religious Education Curriculum - Ana Cahayani Fatimah; ST. Wardah Hanafie Dos (Fitrah, 2026)
Cultural, religious, and ethnic diversity is a social reality that is inseparable from the context of education in Indonesia and the global world. Islamic Religious Education (PAI), as a subject oriented towards the formation of character and spiritual values, is required to be able to respond constructively to the complexity of multiculturalism. This article aims to analyze and formulate a model of integration of multicultural values in the Islamic Religious Education curriculum that is oriented towards strengthening attitudes of tolerance, inclusivity, and religious moderation. This study uses a qualitative approach with a systematic literature study method on relevant national and international literature in the range of 2015–2025. The results of the study show that the integration of multicultural values in the PAI curriculum can be carried out through three main dimensions, namely integration into curriculum objectives, learning content, and pedagogical strategies. The novelty of this article lies in the development of an integrative framework based on a holistic approach that combines wasathiyah Islamic values, critical pedagogy, and contextual learning in response to the challenges of contemporary multicultural education. This article contributes theoretically and practically to the development of a PAI curriculum that is relevant to a pluralistic society.